2019
DOI: 10.1017/s0269889719000231
|View full text |Cite
|
Sign up to set email alerts
|

Blood purity and scientific independence: blood science and postcolonial struggles in Korea, 1926–1975

Abstract: ArgumentAfter World War II, blood groups became a symbol of anti-racial science. This paper aims to shed new light on the post-WWII history of blood groups and race, illuminating the postcolonial revitalization of racial serology in South Korea. In the prewar period, Japanese serologists developed a serological anthropology of Koreans in tandem with Japanese colonialism. The pioneering Korean hematologist Yi Samyŏl , inspired by decolonization movements during the 1960s, excavated and appropriated colonial ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Japanese scientists carried out a number of serologic studies to assess biochemical race indices in East Asian countries. 107,108 Studies repeatedly reported that the Japanese had higher index scores compared to other Asians in their colonies, suggesting the biological superiority of the Japanese race. 109 These research findings played a role for justifying Japan's occupation over East Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese scientists carried out a number of serologic studies to assess biochemical race indices in East Asian countries. 107,108 Studies repeatedly reported that the Japanese had higher index scores compared to other Asians in their colonies, suggesting the biological superiority of the Japanese race. 109 These research findings played a role for justifying Japan's occupation over East Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…일부 보건학 전문가들과 의과대학 교수들은 사설을 통해 일반인들이 마스크를 착용하는 습관은 “2차 대전기 일본에 의해 만들어진” 것이라며 과학적으로는 오히려 “해롭다”는 의견을 제시하기 시작했다. 61) 이처럼 식민지 조선의 마스크 착용 실천의 역사가 재발명되고 마스크 착용이 과학적으로 부적절한 것으로 재정의되는 과정은 당시 남한에서 진행되던 의학적, 과학적 탈식민화 기획들과 적어도 간접적으로나마 연결되어 있었겠지만, 이에 관한 연구는 추후 과제로 남겨둔다( Kim, 2016 ; Hyun, 2019 ).…”
Section: 결론unclassified
“…For instance, Jaehwan Hyun’s research demonstrates that Japanese scientists determined biological superiority based on “scientific” findings achieved through “comparative research on physical and mental traits among Japanese, Korean, and mixed-race children” (2019b: 494). Elsewhere, Hyun also traces—based on Eiji Oguma’s (2002) work A Genealogy of Japanese Self-Images —the historical connection between Japanese and German eugenicists and how Japanese physicians were “inspired by Nazi Germany’s racial hygiene policies” (2019a: 245) to “establish the uniqueness and superiority of the Japanese race, assuming the blood purity” (2019a: 240) of their people.…”
mentioning
confidence: 99%